The Potential of Biomass Energy in Three Nusa Islands - A. A. K. S. Dharmika; I N. Setiawan; W. G. Ariastina; I. A. D. Giriantari; I W. Sukerayasa; I N. S. Kumara (Institute for Research and Community Services Udayana University, 2025)
The Three Nusa Islands consist Nusa Penida, Nusa Lembongan, and Nusa Ceningan are facing increased energy demands due to growing tourism, population, and economic activity. Biomass energy, as a renewable and locally available energy source, presents a viable solution to help meet the island’s sustainable energy needs. This review explores the potential of biomass energy in the region, focusing on the availability of biomass feedstock, technological feasibility, environmental impact, and social acceptance. The study is based on secondary data from government reports, academic journals, and regional statistics, aiming to contribute to the development of decentralized and sustainable energy strategies in Eastern Indonesia.